A relativistic approach to teaching electrodynamics: Deriving Maxwell's equations from first principles - Oleksandr A. Konoval (Science Education Quarterly)
This paper presents a novel methodology for teaching classical electrodynamics based on special relativity theory. Traditional approaches often rely heavily on empirical laws, potentially obscuring the fundamental unity of electromagnetic phenomena. We demonstrate how the core principles of electrodynamics, including Maxwell's equations, can be derived from just two fundamental postulates: the principle of relativity and Coulomb's law. By consistently applying relativistic reasoning, we show how key concepts such as the Lorentz force, Biot-Savart law, and electromagnetic induction emerge naturally. This approach provides a logically coherent framework for understanding electrodynamics, emphasizes its inherently relativistic nature, and resolves apparent paradoxes that arise in non-relativistic treatments. We discuss the pedagogical advantages of this method, including its potential to foster deeper conceptual understanding and develop students' theoretical reasoning skills. The paper also addresses practical aspects of implementing this approach in higher education physics curricula and its implications for physics education research.